Hospital Transfer Network Structure as a Risk Factor for Clostridium difficile Infection - Simmering, Jacob E. (Infect Control Hosp Epidemiol, 2015)
OBJECTIVE: To determine the effect on inter-hospital patient sharing via transfers on the rate of Clostridium difficile infections (CDI) in a hospital. DESIGN: Retrospective cohort METHODS: Using data from the Healthcare Cost and Utilization Project California State Inpatient Database, 2005–2011, we identified 2,752,639 transfers. We then constructed a series of networks detailing the connections formed by hospitals. We computed two measures of connectivity, indegree and weighted indegree, measuring the number of hospitals from which transfers into a hospital arrive, and the total number of incoming transfers, respectively. We estimated a multivariate model of CDI cases using the log-transformed network measures as well as covariates for hospital fixed effects, log median length of stay, log fraction of patients aged 65 or older, quarter and year indicators as predictors. RESULTS: We found an increase of one in the log indegree was associated with a 4.8% increase in incidence of CDI (95% CI: 2.3–7.4) and an increase of one in log weighted indegree was associated with a 3.3% increase in CDI incidence (95% CI: 1.5–5.2). Moreover, including measures of connectivity in the models greatly improved their fit. CONCLUSIONS: Our results suggest infection control is not under the exclusive control of a given hospital but is also influenced by the connections and number of connections that hospitals have with other hospitals.